Pengembangan Wisata Spiritual di Desa Ped Nusa Penida - I Made Mardika; Ni Made Jaya Senastri; I Putu Yudi Prabhadika (Universitas Warmadewa, 2022)
The Community Partnership Program (PKM) on the Development of Spiritual Tourism in Ped Nusa Penida Village aims to empower community groups in realizing the Penataran Ped Temple as spiritual tourism. The target partner is Kelian Pura Penataran Ped. The problems faced by partners are: (1) there is no collaboration between related institutions in the management of spiritual tourism, (2) there is no legal umbrella and contract for the use of temples as spiritual tourism, (3) there is no adequate information regarding the existence of Penataran Ped Temples, and (4) there is no integrated waste management effort to create a clean and comfortable temple environment. Activities carried out as a solution to solving the problem are counseling on tourism management with a model of collaboration and coordination of stakeholders in tourism services, compiling a legal umbrella for religious tourism and contract law for tourism actors, procuring trilingual information boards, designing a mapping and master plan for Penataran Ped Temples, and mentoring integrated waste management. With the community empowerment strategy, it is hoped that it will be able to realize the spiritual tourism of Penataran Ped Temple which will have an impact on improving the community's economic sector.